The Tendency of Human Dignity of Thai Citizens in Assumption of Patronage Politics - Jantaratim, Kasemsanta (Rajapark Journal, 2025)
This article aims to present the trend of the human dignity situation of Thai citizens in practice in society based on the assumption of patronage politics under the democratic regime. The data were collected using the document research method. The results of the study found that the tendency of Thai citizens have only being patrons by state, as of the patronage political system, which uses the mechanism and relationships with the elites, domestic and international capitalists, together with powerful of political and all of groups civil servants. The tendency of the government to be an oligarchy, because of the role and sovereignty of Thai citizens on elections were reduced. As to raise the value of human dignity of Thai citizens to a higher level, Thai citizens must first thoroughly understand their rights, freedoms, and the value of human dignity according to the law. At the same time, academics, lawyers, and Thai citizens jointly promote the decentralization of power to all parts of the country. In addition, educational institutions, mass media organizations, and Thai citizens have joined the campaign to develop human rights and human dignity of Thai citizens to be more stable.